La sapienza [videorecording (DVD)] - Green, Eugène, 1947-; Rongione, Fabrizio; Prot, Christelle; Succio, Ludovico (Kino Lorber, 2015)
Alexandre decides to set off for Italy with the idea of completing his draft of a book on Borromini, and his wife Alienor comes along. Once there, they meet Goffredo, who is set to embark in architectural studies, and Lavinia, who is suffering from a nervous disorder. Alienor decides to stay to help Lavinia, and Alexandre continues on his travels with Goffredo. This separation for husband and wife will be the start of an inner journey for them both.